Tendências nas Hospitalizações por Insuficiência Cardíaca durante um Período de Dezasseis Anos: Dados de Abrangência Nacional para Portugal - José Paulo Santos Ferreira (2022)
Aims: Heart failure (HF) is a major public health problem. This study aimed to describe and characterize all adult hospitalizations from 2000 to 2015 with a primary or secondary diagnosis of HF. Methods and Results: This cross-sectional observational study was conducted using an administrative database, which contains all public heart failure hospitalizations recorded in mainland Portugal, and demographic data from the National Institute of Statistics. Comparative analyses were performed to assess hospitalization trends for key indicators such as absolute and relative frequency, in-hospital mortality, home discharges and length of stay over time and for different age and gender strata. A total of 286783 hospitalizations with HF as primary diagnosis were identified. Patients were principally female (55.0%), mean age was of 76.8 years (SD: 11). Admissions were mostly emergent (95.4%), and median LoS was 7 days (Q1-Q3: 4-12). In-hospital relative mortality was 13.0% and decreased over the study years. There were 671827 hospitalizations with HF as secondary diagnosis, most of these (17.9%) with a principal diagnosis of Pneumonia and the in-hospital mortality was 16.2 and 22.8%, respectively. Conclusions: HF hospitalizations represent 2.3% of all adult hospitalizations and increased across the years. HF codified as a secondary diagnosis is 2.3 times more prevalent than as a primary diagnosis and has had a steeper increase. In-hospital mortality is high when HF is codified as primary diagnosis but even higher when as a secondary diagnosis. The real burden of HF might be underestimated.